MODEL OF CONTENT AND LANGUAGE INTEGRATED LEARNING (CLIL) STRATEGY IN ARABIC SPEAKING SUBJECT - Mohamad Sarip (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2019)
The aim of this study was to develop Arabic speaking skill by implementing Content Language Integrated Learning (CLIL) model at Jakarta State University. The CLIL used in the lesson emphasized the memorization of dialogues and sentence patterns as one of the main characteristics of the audiolingual method. The research employed the mixed approach using Research and Development (R & D). The procedure of research used Borg and Gall model which has the steps; preliminary step, adevelopment step, and evaluation step.The data ware taken by observation, questionnaire, interview, documentation, and test. The research finding shows that the development of CLIL learning strategy for Arabic speaking with the material using Qur’an, Hadits, Fiqih and Tsaqofah Islamiah was an effective model for improving learning to speak Arabic. CLIL have four components that are content, cognition, communication, and culture. These are integrated with the variation of learning media.